Influence of Marketing Mix and Consumer Attitudes Regarding Purchase Decisions Through Brand Image As a Mediating Variable to (Kentucky Fried Chicken Lampung) - CAHAYA, Anggelina Tyo; MS, Mahrinasari; PANDJAITAN, Dorothy RH (PT Keberlanjutan Strategis Indonesia, 2024)
The research was conducted to determine the effect of the marketing mix on purchasing decisions, consumer attitudes towards purchasing decisions, marketing mix on brand image, consumer attitudes towards brand image and brand image mediating the marketing mix and consumer attitudes towards purchasing decisions, this research uses the SEM analysis tool- This PLS research is quantitative with a sample size of 387 with Stratified Random sampling. The empirical findings obtained are that the Marketing Mix is ??Positive and Significant to Purchasing Decisions at KFC in Lampung Province, which means that the Marketing Mix increases, which will increase purchasing decisions. Positive and Significant Consumer Attitudes towards KFC Purchasing Decisions in Lampung Province, can be interpreted as increasing Consumer Attitudes. this will increase Purchasing Decisions. The Marketing Mix is ??Positive and Significant to the brand image at KFC Lampung Province, which means that an Increased Marketing Mix will Improve Brand Image. Consumer Attitudes are Positive and Significant towards the Brand Image at KFC Lampung Province, which can be interpreted as increasing Consumer Attitudes which will increase the brand image of the Marketing Mix in the Mediating of Brand Image towards Positive and Significant Purchasing Decisions, which can be interpreted as Brand Image being able to mediate the Marketing Mix in purchasing decisions at KFC Lampung Province. Consumer attitudes mediated by brand image can be interpreted as positive and significant purchasing decisions, it can be interpreted as brand image being able to mediate consumer attitudes towards purchasing decisions at KFC Lampung Province.